In vitro Interactions of Secnidazole and Its Iron (II), Copper (II) Complexes with Bovine Serum Albumin by Fluorescence Quenching Method (Bangladesh Pharmaceutical Journal, 2020)
The current study was designed to investigate the interactions of an antimicrobial drug secnidazole and its two transition metal complexes with bovine serum albumin (BSA). The interactions of secnidazole and its both transition metal complexes were confirmed by the extingushing of fluorescence intensity of the protein. The fluorescence quenching of BSA by the drug and its both metal complexes showed a static quenching process and the reactions followed exothermic mechanism. The fluorescence spectroscopic method was utilized to evaluate the thermodynamic parameters like change of enthalpy (ΔH), entropy (ΔS) and Gibb’s free energy (ΔG) which indicated the bindings of the antimicrobial agent and its both metal chelates were hydrogen bonding and van der Waals interactions. The binding constant and the number of binding sites were also measured by double log plot that indicated the drug or its metal complexes bound with BSA at 1:1 ratio.Bangladesh Pharmaceutical Journal 23(1): 1-9, 2020